Low-loss dielectric constant polyphenyl ether-based material based on supercritical carbon dioxide foaming

By introducing the micro -pore structure of supercritical carbon dioxide foaming in polystyrene and high -density polyethylene composite materials, the problem of high -frequency applications in high -frequency application agencies in high -frequency application agencies and high losses are solved. The dielectric constant and low -loss polystylene ether -based material are suitable for high -frequency communication equipment.

CN119371806APending Publication Date: 2025-01-28得彩新材料(山东)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411447909.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing low-dielectric constant materials have high dielectric constant and losses in high-frequency applications, which cannot fully meet the demand for high-performance materials of modern communication devices. At the same time, the poor dispersion of nanofillers and the complex chemical foaming process lead to uneven material properties.

Method used

The low -loss agglutonine constant polyetherene base material based on supercritical carbon dioxide foam is used, and a uniform microporous structure is introduced by the introduction of a uniform microporous structure in polystyrene ether and high -density polyethylene composite materials to reduce the consumption loss of the dielectric.

Benefits of technology

The low -agent constant and low loss characteristics of the material are realized, while maintaining the temperature and thermal stability of high glass transformation, it is suitable for high temperature environments, and the process is simple and environmentally friendly, and the material performance is uniform and stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371806A_ABST
    Figure CN119371806A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer composite materials and high-frequency communication materials, and discloses a supercritical carbon dioxide foaming-based low-loss dielectric constant polyphenyl ether-based material which is prepared from the following components in parts by mass: 90-80 parts of polyphenyl ether, 10-20 parts of high-density polyethylene and an antioxidant accounting for 0.5% of the mass of the high-density polyethylene, the preparation method comprises the following steps: 1, material selection: selecting polyphenyl ether as a base material and high-density polyethylene as a secondary phase material; and 2, drying treatment: drying the polyphenyl ether powder at 110 DEG C for 12 hours, and drying the high-density polyethylene particles at 60 DEG C for 12 hours. A uniform microporous structure is introduced into the polyphenyl ether and high-density polyethylene composite material, so that the dielectric constant of the material is remarkably reduced, and the introduction of the microporous structure enables the material to contain air components with low dielectric constants, so that the dielectric constant of the composite material is integrally reduced, and meanwhile, the polarization effect in an electric field is reduced; and the dielectric loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials and high-frequency communication materials, in particular to a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming. Background Art

[0002] With the continuous development of electronic communication technology, especially the popularization of 5G and high-frequency communication technology, the demand for low-loss, high-frequency and stable dielectric materials in electronic devices continues to grow. Low-loss dielectric materials exhibit excellent electrical properties during high-frequency signal transmission, ensuring stable signal transmission with low attenuation. Therefore, the development of polymer materials with low dielectric constant, low loss and excellent thermal properties is of great significance to improving the performance of communication equipment.

[0003] Most of the existing low dielectric constant materials are based on organic polymers, such as epoxy resins, polyimides, cyanate resins, and fluorinated polymers. These materials usually reduce the dielectric constant and dielectric loss of the materials by introducing nanofillers into the matrix and chemical foaming. However, in high-frequency applications, the dielectric constant and loss of traditional organic materials are usually high, and cannot fully meet the needs of modern communication devices for high-performance materials. At the same time, the dispersion of nanofillers in the matrix is ​​poor, which can easily cause uneven material properties and lead to unstable electrical properties; while the chemical foaming process is prone to problems such as uneven pore size and uneven pore distribution, resulting in poor performance of the material in terms of dielectric and mechanical properties. In addition, chemical foaming agents remaining in the material will introduce polar impurities, further affecting the material performance, and the process is complicated, which is not conducive to large-scale industrial production.

[0004] The main problem in the existing technology is that although the dielectric constant has been reduced through various technical means, the overall performance of the material, including dielectric loss, thermal stability, processability, and environmental protection characteristics, is still insufficient, making it difficult to meet the requirements of high-frequency communication equipment for high-performance, low-loss dielectric materials. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming, which solves the problem that the dielectric constant and loss of traditional organic materials are usually high and cannot fully meet the needs of modern communication devices for high-performance materials.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming, the material is made of the following components in a mass ratio: 90-80 parts of polyphenylene ether, 10-20 parts of high-density polyethylene, and an antioxidant, accounting for 0.5% of the mass of the high-density polyethylene.

[0007] The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming comprises the following steps:

[0008] Step 1, material selection: polyphenylene ether is selected as the matrix material, high-density polyethylene is selected as the secondary phase material, and an antioxidant is added to mix and prepare the raw material, wherein the amount of the antioxidant is 0.5% of the mass of the high-density polyethylene;

[0009] Step 2, drying treatment: drying the polyphenylene ether powder at 110° C. for 12 hours and drying the high-density polyethylene particles at 60° C. for 12 hours to remove moisture;

[0010] Step 3, melt blending: In a twin-screw micro-compounder, the dried polyphenylene ether powder, high-density polyethylene particles and antioxidant are melt blended, the mixing temperatures from the feed port to the die head are set to 275° C., 280° C., and 280° C., the screw speed is 100 rpm, and the mixing time is 10 minutes to obtain a blended composite material;

[0011] Step 4: Granulation: The melt-blended composite material is cooled to room temperature and formed into 1.5 mm particles using a granulator;

[0012] Step 5, hot pressing: preparing a sample of a specific size by hot pressing the particles at 275° C., preheating the plate and particles, the hot pressing pressure is 10 MPa, and the hot pressing time is 10 minutes;

[0013] Step 6: Supercritical carbon dioxide foaming: Place the hot-pressed sample in a high-pressure reactor, introduce carbon dioxide at a set temperature of 180°C to 220°C and a pressure of 10 MPa, and the saturation time is 1 hour; after saturation, the reactor pressure is quickly released to drop to atmospheric pressure within 0.5 seconds to generate a microporous structure.

[0014] Preferably, in step six, the supercritical carbon dioxide foaming step comprises:

[0015] In the autoclave, carbon dioxide permeates and dissolves in the polyphenylene ether / high-density polyethylene matrix to form a uniform saturated system;

[0016] After reaching the set saturation time, the saturated system enters a supersaturated state by rapid pressure relief, resulting in the formation of bubble nuclei, which produces a uniform microporous structure in the polyphenylene ether and high-density polyethylene matrix.

[0017] Preferably, in the supercritical carbon dioxide foaming step, the hot-pressed sample is placed in a high-pressure reactor, and carbon dioxide is introduced at a temperature range of 180° C. to 220° C. and a pressure of 10 MPa, and the saturation time is 1 hour to ensure that a uniform microporous structure is formed in the sample.

[0018] Preferably, the melt blending process of the polyphenylene ether and high-density polyethylene composite material adopts a twin-screw micro-mixer, and the mixer has a mixing cavity with a capacity of 15 mL.

[0019] Preferably, the particle size of the polyphenylene ether powder is in the range of 50 to 100 microns.

[0020] Preferably, the mixing chamber capacity of the twin-screw micro-mixer used in the melt blending step is 15 ml, and the screw speed of the mixer is set to 100 rpm to ensure uniform melting and dispersion of the materials.

[0021] Preferably, the mixing temperatures are set to 275° C., 280° C., and 280° C. from the feed port to the die head, and the mixing time is 10 minutes to ensure that the polyphenylene ether and the high-density polyethylene are fully mixed in a molten state to form a composite material.

[0022] Preferably, in the hot pressing step, the granulated particles are placed in a hot pressing mold, the plate and particles are preheated at 275° C. for 5 minutes, and then the hot pressing is maintained at a pressure of 10 MPa for 10 minutes to ensure that the particles soften and flow to form a uniformly formed sample.

[0023] Preferably, in the granulation step, the melt-blended composite material is cooled to room temperature, and the cooled material is formed into granules with a diameter of 1.5 mm using a granulator.

[0024] The invention provides a polyphenylene ether-based material with a low loss dielectric constant based on supercritical carbon dioxide foaming.

[0025] It has the following beneficial effects:

[0026] 1. The present invention introduces a uniform microporous structure into the composite material of polyphenylene ether and high-density polyethylene, and the dielectric constant of the material is significantly reduced, thereby achieving low loss characteristics. This is because the introduction of the microporous structure allows the material to contain air components with low dielectric constants, thereby reducing the dielectric constant of the composite material as a whole, while reducing the polarization effect in the electric field and reducing the dielectric loss.

[0027] 2. The present invention adopts an incompatible system of polyphenylene ether and high-density polyethylene, so that the material maintains a high glass transition temperature and thermal stability while maintaining low dielectric properties, and is suitable for applications in high-temperature environments. This characteristic ensures that the thermal expansion coefficient of the material is low and avoids performance degradation at high temperatures.

[0028] 3. The present invention can precisely control the size, distribution and expansion ratio of micropores in the material by regulating the process parameters such as temperature, pressure and time of supercritical carbon dioxide foaming, thereby customizing the dielectric properties and density of the material. This controllability makes the design and application range of the material wider and can meet the needs of different high-frequency communication equipment.

[0029] 4. The present invention avoids the disadvantage of introducing high-polarity residues by using supercritical carbon dioxide as a foaming agent. No harmful substances are generated during the foaming process and there is no pollution to the material, which meets the requirements of green environmental protection process. The entire foaming process is simple, which is conducive to the high purity and stable performance of the material.

[0030] 5. The present invention uses a supercritical carbon dioxide foaming process to make the internal micropore structure of the material uniform and stable, and the pore size distribution is consistent, avoiding the problems of uneven pore size and uneven pore distribution in the traditional chemical foaming method, making the electrical and mechanical properties of the material more uniform and stable, and improving the reliability of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of dielectric constant of the present invention;

[0032] Figure 2 Schematic diagram of dielectric loss tangent of the present invention;

[0033] Figure 3 It is a schematic diagram of the storage modulus of the present invention;

[0034] Figure 4 It is a schematic diagram of the complex viscosity of the present invention;

[0035] Figure 5 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Embodiment 1:

[0038] The embodiment of the present invention provides a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming. The material is made of the following components in a mass ratio: 90-80 parts of polyphenylene ether, 10-20 parts of high-density polyethylene, and an antioxidant, which accounts for 0.5% of the mass of the high-density polyethylene.

[0039] Embodiment 2:

[0040] Please see attached Figure 1 - Attachment Figure 5 This embodiment provides a method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming on the basis of the above embodiment, comprising the following steps:

[0041] Step 1, material selection: polyphenylene ether is selected as the matrix material, high-density polyethylene is selected as the secondary phase material, and an antioxidant is added to mix and prepare the raw material, and the amount of the antioxidant is 0.5% of the mass of the high-density polyethylene;

[0042] Step 2: Drying: Dry the polyphenylene ether powder at 110° C. for 12 hours and dry the high-density polyethylene particles at 60° C. for 12 hours to remove moisture;

[0043] Step 3, melt blending: In a twin-screw micro-compounder, the dried polyphenylene ether powder, high-density polyethylene particles and antioxidant are melt blended, the mixing temperatures from the feed port to the die head are set to 275° C., 280° C., and 280° C., the screw speed is 100 rpm, and the mixing time is 10 minutes to obtain a blended composite material;

[0044] Step 4: Granulation: The melt-blended composite material is cooled to room temperature and formed into 1.5 mm particles using a granulator;

[0045] Step 5, hot pressing: prepare samples of specific size by hot pressing the particles at 275°C, preheat the plate and particles, the hot pressing pressure is 10 MPa, and the hot pressing time is 10 minutes;

[0046] Step 6: Supercritical carbon dioxide foaming: Place the hot-pressed sample in a high-pressure reactor, introduce carbon dioxide at a set temperature of 180°C to 220°C and a pressure of 10 MPa, and the saturation time is 1 hour; after saturation, the reactor pressure is quickly released to drop to atmospheric pressure within 0.5 seconds to generate a microporous structure.

[0047] In step six, the supercritical carbon dioxide foaming step includes:

[0048] In the autoclave, carbon dioxide permeates and dissolves in the polyphenylene ether / high-density polyethylene matrix to form a uniform saturated system;

[0049] After reaching the set saturation time, the saturated system enters a supersaturated state by rapid pressure relief, resulting in the formation of bubble nuclei, which produces a uniform microporous structure in the polyphenylene ether and high-density polyethylene matrix.

[0050] In the supercritical carbon dioxide foaming step, the hot-pressed sample is placed in a high-pressure reactor, and carbon dioxide is introduced at a temperature range of 180°C to 220°C and a pressure of 10 MPa. The saturation time is 1 hour to ensure the formation of a uniform microporous structure in the sample.

[0051] The melt blending process of the polyphenylene ether and high-density polyethylene composite material adopts a twin-screw micro-mixer, and the mixer has a mixing cavity with a capacity of 15 mL.

[0052] The particle size of the polyphenylene ether powder ranges from 50 to 100 microns.

[0053] The mixing chamber capacity of the twin-screw micro-mixer used in the melt blending step is 15 ml, and the screw speed of the mixer is set to 100 rpm to ensure uniform melting and dispersion of the materials.

[0054] The mixing temperatures were set to 275° C., 280° C., and 280° C. from the feed port to the die head, and the mixing time was 10 minutes to ensure that the polyphenylene ether and the high-density polyethylene were fully mixed in a molten state to form a composite material.

[0055] In the hot pressing step, the granulated particles are placed in a hot pressing mold, the plate and particles are preheated at 275°C for 5 minutes, and then the hot pressing is maintained at a pressure of 10 MPa for 10 minutes to ensure that the particles soften and flow and form a uniformly formed sample.

[0056] In the granulation step, the melt-blended composite material is cooled to room temperature, and the cooled material is formed into granules with a diameter of 1.5 mm using a granulator.

[0057] In one embodiment, in step one, the material selection involved includes the following details:

[0058] Base material: polyphenylene ether (PPE)

[0059] As a matrix material, PPE plays a role in providing the main properties of the material in the present invention. The reason for selecting PPE is its excellent electrical insulation performance, thermal stability and adjustable mechanical properties. In this embodiment, Asah iXYRONTM S201A model PPE powder is selected. This model of PPE has a high glass transition temperature and excellent melt flow performance, which meets the processing requirements under high temperature. In addition, the particle size range of PPE powder is controlled to be 50 to 100 microns. This particle size range not only ensures its uniform dispersibility during the melt blending process, but also does not affect the processing performance of the material. The particle size control of PPE can be achieved by mechanical crushing and screening operations to ensure that the powder has a uniform particle size distribution.

[0060] Secondary phase material: High density polyethylene (HDPE)

[0061] In order to improve the processing properties of PPE and reduce its melt viscosity, HDPE is introduced as a secondary phase material. HDPE has good fluidity and mechanical properties, and can form a blending system with PPE during melt blending, thereby improving the processing properties of the overall material. In this embodiment, NOVA Chemical SCLAI R 2807 model HDPE particles are selected, and the particle size range is between 2 and 4 mm. Such a particle size can ensure uniform dispersion during the blending process, and is also conducive to full mixing with PPE powder. The selection of HDPE is based on its lower melting temperature and good compatibility, ensuring that the material properties will not be adversely affected during the co-blending foaming process.

[0062] Additives: Antioxidants

[0063] Since the subsequent melt blending and processing may involve high temperature treatment, in order to prevent the HDPE from oxidative degradation, an antioxidant needs to be added to stabilize the thermal properties of HDPE. 1010 Antioxidant. The amount of antioxidant added is 0.5% of the mass of HDPE, which is sufficient to inhibit the oxidative degradation of HDPE without adversely affecting the final properties of the material. The antioxidant can be evenly dispersed during the blending of HDPE and PPE, and provide stable thermal properties during subsequent processing.

[0064] Material quality ratio

[0065] In the present invention, the mass ratio of PPE to HDPE is controlled between 90-80 parts of PPE and 10-20 parts of HDPE. By adjusting the ratio of the two, the processing properties and dielectric properties of the material can be changed to meet different application requirements. The selected antioxidant addition ratio is fixed at 0.5% of the HDPE mass to ensure that the material remains stable during processing and final application.

[0066] In the material preparation process, the drying treatment in step 2 is crucial to ensure the purity and processing performance of the material. The purpose of the drying treatment is to remove moisture from the material to prevent the generation of bubbles, material degradation or processing instability caused by water evaporation or decomposition during the subsequent melt blending, granulation and molding processes. In addition, by reasonably controlling the drying temperature and time, it is ensured that the material will not degrade or other property changes occur, providing suitable conditions for subsequent processes. Therefore, the drying treatment in step 2 is a key prerequisite for ensuring the uniformity and stability of the material.

[0067] In this embodiment, the drying process includes the following operations:

[0068] Drying of polyphenylene ether (PPE) powder

[0069] The selected PPE powder is dried to remove the hygroscopic moisture in the powder to ensure that it does not hydrolyze or foam during the melt blending process. In this embodiment, the PPE powder is placed in a vacuum drying oven and dried at a temperature of 110°C for 12 hours. The drying temperature of 110°C is lower than the glass transition temperature of PPE, so it will not cause the powder to melt or the polymer to degrade. The vacuum drying method helps to quickly remove moisture from the material at a lower temperature, improve the drying efficiency, and prevent oxidation or moisture on the surface of the PPE powder.

[0070] Drying of high density polyethylene (HDPE) granules

[0071] HDPE particles are easy to soften or even melt at high temperatures, so the selection of drying temperature and time is particularly critical. In this embodiment, the HDPE particles are dried at 60°C for 12 hours. This drying temperature is lower than the melting point of HDPE, and can effectively remove moisture from the HDPE particles without causing the particles to agglomerate or change their morphology. The drying of HDPE is also carried out under vacuum conditions to ensure that the moisture inside and on the surface of the particles can be fully removed, ensuring that no bubbles or uneven processing occur during subsequent melt blending.

[0072] Drying time and storage

[0073] For the drying of PPE and HDPE, a drying time of 12 hours is selected to ensure that the moisture in the material is fully removed without affecting the fluidity and processing performance of the material. The dried PPE powder and HDPE granules should be immediately sealed and stored in a dry container to avoid re-absorption of moisture and ensure that they remain dry in subsequent steps.

[0074] In the embodiment, melt blending

[0075] In this embodiment, melt blending is to fully mix PPE and HDPE to form a uniform composite material, and at the same time, to evenly distribute the antioxidant in the composite material.

[0076] Material mixing: Mix the dried PPE powder, high-density polyethylene particles and antioxidant according to the set mass ratio (PPE: HDPE: antioxidant = 90-80: 10-20: 0.5%). Mix the raw materials evenly so that the components can be fully contacted and dispersed during melt blending.

[0077] Melt blending conditions: A twin-screw micro-compounder (Xplore MC15) was used for melt blending. The mixing chamber capacity of the mixer was 15 ml to ensure that the appropriate amount of material could be effectively mixed. The mixing temperature was set to 275°C, 280°C, and 280°C from the feed port to the die head, the screw speed was maintained at 100 rpm, and the mixing time was 10 minutes. The temperature setting was based on the melting point and rheological properties of PPE and HDPE to ensure that the two could be fully mixed in the molten state.

[0078] Blending results: The composite material after blending is in a uniform mixed state, the HDPE particles are evenly dispersed in the PPE matrix, and the antioxidant has been evenly distributed in the HDPE to ensure the thermal stability of the material.

[0079] In the embodiment, granulation

[0080] In this embodiment, granulation is performed to prepare granular materials suitable for subsequent hot pressing.

[0081] Granulation step: The blended composite material is cooled to room temperature. The temperature should be slowly lowered during the cooling process to prevent stress from being generated inside the material, which may cause the particles to break or become uneven. The cooled material is prepared into particles with a diameter of 1.5 mm using a granulator. During the granulation process, the particles are ensured to be uniform in shape and size.

[0082] Granule storage: Granulated granules should be stored in a sealed and dry environment to prevent the granule surface from absorbing moisture or being contaminated, thus ensuring the quality in the subsequent hot pressing process.

[0083] In the embodiment, hot pressing

[0084] In this embodiment, the hot pressing step is to press the granulated particles into sheets of a specific size to serve as the basic material for subsequent supercritical carbon dioxide foaming.

[0085] Hot Pressing Process: Place the granulated particles in a hot press molding mold and place the mold in a hot press. Preheat the mold and particles at 275°C for 5 minutes to ensure that the particles soften in the mold and begin to flow. Then apply a pressure of 10MPa to the mold and keep the hot pressing time for 10 minutes. During the hot pressing process, the particles fuse under pressure and high temperature to form a uniform sheet.

[0086] Cooling and demoulding: After hot pressing, the sample and the mold are slowly cooled to room temperature to avoid internal stress in the sheet. After cooling, the sample is demoulded to obtain a sheet sample of a specific size, ready for the next step of supercritical carbon dioxide foaming.

[0087] In the embodiment, supercritical carbon dioxide foaming

[0088] In this embodiment, the supercritical carbon dioxide foaming step is to reduce the dielectric constant and dielectric loss by introducing a microporous structure into the composite material.

[0089] Supercritical carbon dioxide saturation treatment: Place the hot-pressed sheet sample in a high-pressure reactor. Set the reactor temperature to 180°C to 220°C and the pressure to 10MPa. Under this condition, carbon dioxide is introduced, and it will penetrate into the sheet and form a uniform saturated system with the matrix material. Keep the saturation time for 1 hour to ensure that the carbon dioxide fully penetrates.

[0090] Rapid pressure relief foaming: After saturation is completed, the pressure of the reactor is rapidly reduced from 10MPa to atmospheric pressure within 0.5 seconds through rapid pressure relief. Due to the sudden drop in pressure, the carbon dioxide inside the composite material is supersaturated, forming bubble nuclei and producing a uniform microporous structure.

[0091] Stable microporous structure: The foamed sample is taken out of the reactor and immediately placed in water for cooling to prevent the microporous structure from collapsing or closing during the cooling process and to ensure uniform pore size and distribution.

[0092] In the implementation, material performance testing and analysis

[0093] The foamed sheets are tested for performance to ensure that the material has the required low loss, low dielectric constant and excellent thermal properties.

[0094] Dielectric performance test: Use dielectric testing instruments to measure the dielectric constant and dielectric loss tangent of the material to determine whether the foamed material meets the design requirements and achieves the effect of low dielectric loss.

[0095] Thermal performance test: Use thermogravimetric analyzer (TGA) and differential scanning calorimeter (DSC) to determine the glass transition temperature and thermal stability of the material to ensure that the material is suitable for high temperature environments.

[0096] Micropore structure observation: Use a scanning electron microscope (SEM) to observe the micropore structure of the material to confirm the size, distribution and uniformity of the micropores to verify the effect of the foaming process.

[0097] Preferred embodiment 1: Process optimization of adjusting drying temperature and time

[0098] In this preferred embodiment, the drying conditions of the PPE powder and HDPE granules are further optimized to ensure efficient removal of moisture while avoiding any potential material degradation and ensuring stable processing quality.

[0099] Further optimization of PPE powder drying

[0100] When selecting the drying temperature, the glass transition temperature and thermal stability of PPE were taken into consideration, and the drying temperature was further increased from 110°C to 120°C. This temperature range is still within the stable state of PPE, ensuring that the material will not decompose or break any molecular chains. To ensure sufficient drying, the PPE powder was dried under vacuum conditions for 8-10 hours. Shortening the drying time can effectively improve production efficiency.

[0101] Control of vacuum drying: During the drying process, the vacuum degree is maintained between 0.05-0.1MPa to reduce the boiling point of water and ensure rapid removal of water at a lower temperature. The stability of temperature and vacuum degree is monitored during the drying process to avoid temperature fluctuations that may cause changes in material properties or poor drying results.

[0102] Further optimization of HDPE granule drying

[0103] Considering the crystallization characteristics and melting point of HDPE (about 130°C), increasing the drying temperature from 60°C to 70°C can more effectively remove moisture without causing deformation or agglomeration of the material. At the same time, the drying time is shortened to 10 hours. The drying temperature of 70°C is within the crystallization temperature range of HDPE, so it will not cause adhesion or melting of the material particles.

[0104] Control of drying environment: Keep the air humidity below 10% during the drying process to accelerate the evaporation of water in the HDPE particles. You can add a desiccant or use circulating air in the drying box to maintain a dry environment.

[0105] Treatment of dried materials

[0106] Storage after drying: Seal the dried PPE powder and HDPE granules and store them in vacuum sealed bags or dry containers to avoid secondary moisture absorption. The materials should be kept in a dry environment during storage to prevent excessive humidity from affecting the material properties.

[0107] Through the above process optimization, the drying process can be carried out more efficiently, ensuring the stable quality of the material during processing and avoiding moisture interference with the subsequent melt co-mixing and molding steps.

[0108] Preferred embodiment 2: Material surface treatment to improve interface compatibility

[0109] In this preferred embodiment, the HDPE particles are subjected to surface modification treatment in order to enhance the interfacial compatibility between HDPE and PPE, improve the uniformity of the material after melt blending, and further improve the electrical and mechanical properties of the material.

[0110] Selection and dosage of coupling agent

[0111] Coupling agent selection: Selecting a suitable coupling agent can enhance the interaction between HDPE and the PPE matrix. In this embodiment, a silane coupling agent (such as KH-550, γ-aminopropyltriethoxysilane) or a titanate coupling agent (such as NDZ-201) can be used, and the specific selection depends on the target performance and processing technology of the material. Silane coupling agents usually have good interfacial adhesion properties and can form chemical bonds with the long chain structure of HDPE and the functional groups of the PPE matrix.

[0112] Coupling agent dosage control: The dosage of coupling agent is 0.5%-1% of the mass of HDPE particles. This ratio ensures that the coupling agent can fully cover the surface of HDPE particles without affecting the flow properties of the material and subsequent processing. Using excessive coupling agent may increase the viscosity of the material and affect the molding fluidity.

[0113] Surface treatment process

[0114] Coupling agent coating: Mix the coupling agent with the HDPE particles according to the above ratio and apply it evenly using a spray device or agitator. The coating process should ensure that the coupling agent is in full contact with the HDPE particles so that a uniform coupling agent film layer is formed on the particle surface.

[0115] Standing and drying: After coating the coupling agent, the HDPE particles are allowed to stand at room temperature for 30 minutes to allow the coupling agent to react with the surface of the HDPE particles and solidify to form a stable interface. Then, a slight drying treatment (about 1-2 hours) is performed at 50°C to ensure that the coupling agent is completely solidified and bonded to the HDPE surface.

[0116] Effect after coupling agent treatment: Through coupling agent treatment, the chemical structure of the surface of HDPE particles changes, increasing the compatibility with the PPE matrix and reducing the interfacial tension between the two phases. In this way, in the subsequent melt blending process, HDPE particles can be better dispersed in the PPE matrix, ensuring the uniformity and stability of the material.

[0117] Improved material performance after surface treatment

[0118] Dispersion uniformity: Through the coating of coupling agent, the dispersion uniformity of HDPE particles in PPE is significantly improved, the particle aggregation phenomenon is reduced, and the microporous structure of the material is ensured to be uniform and stable in the subsequent foaming process.

[0119] Improved material properties: The electrical properties, mechanical properties and thermal stability of the composite materials after surface treatment have been significantly improved. Especially the dielectric properties, the good interface bonding between HDPE particles and PPE reduces the dielectric loss of the composite materials and improves the dielectric constant stability of the materials.

[0120] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming, characterized in that: The material is made of the following components in mass ratio: 90-80 parts of polyphenylene ether, 10-20 parts of high-density polyethylene, and an antioxidant, which accounts for 0.5% of the mass of the high-density polyethylene.

2. A method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming, according to the low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 1, characterized in that: The following steps are involved: Step 1, material selection: polyphenylene ether is selected as the matrix material, high-density polyethylene is selected as the secondary phase material, and an antioxidant is added to mix and prepare the raw material, wherein the amount of the antioxidant is 0.5% of the mass of the high-density polyethylene; Step 2, drying treatment: drying the polyphenylene ether powder at 110° C. for 12 hours and drying the high-density polyethylene particles at 60° C. for 12 hours to remove moisture; Step 3, melt blending: In a twin-screw micro-compounder, the dried polyphenylene ether powder, high-density polyethylene particles and antioxidant are melt blended, the mixing temperatures from the feed port to the die head are set to 275° C., 280° C., and 280° C., the screw speed is 100 rpm, and the mixing time is 10 minutes to obtain a blended composite material; Step 4: Granulation: The melt-blended composite material is cooled to room temperature and formed into 1.5 mm particles using a granulator; Step 5, hot pressing: preparing a sample of a specific size by hot pressing the particles at 275° C., preheating the plate and particles, the hot pressing pressure is 10 MPa, and the hot pressing time is 10 minutes; Step 6: Supercritical carbon dioxide foaming: Place the hot-pressed sample in a high-pressure reactor, introduce carbon dioxide at a set temperature of 180°C to 220°C and a pressure of 10 MPa, and the saturation time is 1 hour; after saturation, the reactor pressure is quickly released to drop to atmospheric pressure within 0.5 seconds to generate a microporous structure.

3. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: In step six, the supercritical carbon dioxide foaming step comprises: In the autoclave, carbon dioxide permeates and dissolves in the polyphenylene ether / high-density polyethylene matrix to form a uniform saturated system; After reaching the set saturation time, the saturated system enters a supersaturated state by rapid pressure relief, resulting in the formation of bubble nuclei, which produces a uniform microporous structure in the polyphenylene ether and high-density polyethylene matrix.

4. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: In the supercritical carbon dioxide foaming step, the hot-pressed sample is placed in a high-pressure reactor, and carbon dioxide is introduced at a temperature range of 180° C. to 220° C. and a pressure of 10 MPa. The saturation time is 1 hour to ensure that the sample forms a uniform microporous structure.

5. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: The melt blending process of the polyphenylene ether and high-density polyethylene composite material adopts a twin-screw micro-mixer, and the mixer has a mixing cavity with a capacity of 15 mL.

6. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: The particle size of the polyphenylene ether powder ranges from 50 to 100 microns.

7. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: The mixing chamber capacity of the twin-screw micro-mixer used in the melt blending step is 15 ml, and the screw speed of the mixer is set to 100 rpm to ensure uniform melting and dispersion of the materials.

8. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: The mixing temperatures were set to 275° C., 280° C., and 280° C. from the feed port to the die head, and the mixing time was 10 minutes to ensure that the polyphenylene ether and the high-density polyethylene were fully mixed in a molten state to form a composite material.

9. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: In the hot pressing step, the granulated particles are placed in a hot pressing mold, the plate and particles are preheated at 275° C. for 5 minutes, and then the hot pressing is maintained at a pressure of 10 MPa for 10 minutes to ensure that the particles soften and flow and form a uniformly formed sample.

10. The method for preparing a low-loss dielectric constant polyphenylene ether-based material based on supercritical carbon dioxide foaming according to claim 2, characterized in that: In the granulation step, the melt-blended composite material is cooled to room temperature, and the cooled material is formed into granules with a diameter of 1.5 mm using a granulator.